2000
DOI: 10.1164/ajrccm.161.5.9905061
|View full text |Cite
|
Sign up to set email alerts
|

Raised Exhaled Nitric Oxide in Healthy Children Is Associated with Domestic Formaldehyde Levels

Abstract: Exposure to domestic levels of formaldehyde has been associated with adverse respiratory symptoms in both adults and children. The underlying mechanisms responsible for these findings have not been established. In order to investigate possible inflammatory effects of formaldehyde at levels typically found in the home, we measured exhaled nitric oxide (eNO) in 224 healthy children 6 to 13 yr of age (116 girls) and monitored formaldehyde levels in their homes. Formaldehyde was monitored using a passive sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 14 publications
5
76
1
5
Order By: Relevance
“…Formaldehyde has been associated with increased prevalence of atopy (Garrett et al, 1999) and higher levels of specific immunoglobulin E (Wantke et al, 1996) in children. Formaldehyde, at levels typically encountered in homes in developed countries, is associated with airway inflammation in both healthy children (Franklin et al, 2000) and adults (Wieslander et al, 1997). Exposing animals to formaldehyde (200 μg/m 3 ) enhances sensitization to inhaled allergens (Riedel et al, 1996), an observation that supports the role of formaldehyde as a cofactor for postnatal Th2 boosting.…”
Section: ) Indoor Airmentioning
confidence: 80%
“…Formaldehyde has been associated with increased prevalence of atopy (Garrett et al, 1999) and higher levels of specific immunoglobulin E (Wantke et al, 1996) in children. Formaldehyde, at levels typically encountered in homes in developed countries, is associated with airway inflammation in both healthy children (Franklin et al, 2000) and adults (Wieslander et al, 1997). Exposing animals to formaldehyde (200 μg/m 3 ) enhances sensitization to inhaled allergens (Riedel et al, 1996), an observation that supports the role of formaldehyde as a cofactor for postnatal Th2 boosting.…”
Section: ) Indoor Airmentioning
confidence: 80%
“…These studies, which investigated children's respiratory health in relation to formaldehyde exposures based on stationary indoor measures, have indicated that respiratory impacts can occur at relatively low concentrations, as are found in conventional Australia homes (Garrett et al 1999;Franklin et al 2000). This further supports the need to more directly quantify the actual concentrations of formaldehyde children are being exposed to.…”
Section: Conclusion and Rationale For Studymentioning
confidence: 86%
“…The primary use of formaldehyde is the production of resins which are used as adhesives in the production of particleboard, fibreboard and plywood, with these products common materials in almost all homes and indoor environments (McPhail 1991;Kelly 1999;Dingle et al 2000;Jiang 2002). …”
Section: Sourcesmentioning
confidence: 99%
See 2 more Smart Citations